Embarazo en la adolescencia: entre el fracaso informativo y el logro psíquico (2013)
ABSTRACT: This research looks into teen pregnancy from a psychoanalytic approach that is based on concepts developed by Freud and others who have worked with teenagers. Primary data were based on a series of interviews. These were subsequently analyzed and the categories that emerged from this analysis were articulated with psychoanalytic concepts regarding this transitional time that is adolescence. This was done so that we could answer the question as to what psychic elements come into play and in part, result in the failure of actions intended to reduce teenage pregnancy by providing information.